Pan-cancer analysis of the prevalence and associated factors of lung metastasis and the construction of the lung metastatic classification system - Lv, Xiaolong; Yang, Lei; Liu, Tianyu; Yang, Zelin; Jia, Chenhao; Chen, Huanwen (Frontiers in Surgery, 2022)
This study first presents an analysis of the prevalence and associated factors of lung metastasis (LM) database and then uses this analysis to construct an LM classification system. Using cancer patient data gathered from the Surveillance, Epidemiology, and End Results (SEER) database, this study showed that the prevalence of LM was not consistent among different cancers, the prevalence of LM ranged from 0.0013 (brain; 95% confidence interval (95% CI); 0.0010 - 0.0018) to 0.234 (“other digestive organs”; 95% CI; 0.221 - 0.249), and found that advanced age, poor grade, higher T or N stage, and metastases including bone, brain, and liver were positively related to LM occurrence, while female gender, income, marital status, and insured status were negatively related, then four categories are generated from 58 cancer types based on prevalence and influence factors and satisfactorily validated. This classification system reflects the LM risk of different cancers. It can guide individualized treatment and the management of these synchronous metastatic cancer patients and help clinicians better distribute medical resources.